1982
DOI: 10.1002/app.1982.070270705
|View full text |Cite
|
Sign up to set email alerts
|

Aminimide as hardener/curing promotor for one part epoxy resin composition

Abstract: SynopsisThree kinds of aminimide compounds were examined as latent hardenedpromotors for epoxy resins. Since aminimides are thermolyzed to generate tertiary amine and isocyanate, the compounds are useful as polymerization initiators for the epoxy group as well as promotors for epoxy-acid anhydride reaction. The pot l i e was over 30 days at 40°C for a formulated one-part epoxy resin system. In comparison with epoxy resins cured with conventional hardeners, several interesting characteristics of the mechanical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…An excellent approach toward the development of latency in curing agents has been demonstrated by the use of aminimide compounds 5. The aminimide contains a ylide structure (N − N + ), which is responsible for the latent properties of these compounds, and it is stable at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…An excellent approach toward the development of latency in curing agents has been demonstrated by the use of aminimide compounds 5. The aminimide contains a ylide structure (N − N + ), which is responsible for the latent properties of these compounds, and it is stable at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…More than three decades ago, reviews suggested that amineimide derivatives can produce tertiary amines and the corresponding isocyanates by pyrolysis 12, 13. Some articles have already proposed to apply amineimide derivatives to epoxide curing systems as thermally latent catalysts or thermally curing agents with the mechanism 14–18. Some reports also have indicated application to photoresists with polarity changes of amineimide moiety by UV irradiation 19, 20.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, thermal/photo dual base catalysts are expected to improve the issue that the photocuring cannot take place smoothly if the materials are not transparent enough toward the photoirradiation (so‐called “photo/thermal dual‐cure”) . Aminimides are attractive candidates for the photo/thermal dual base catalysts, because they are reported to undergo the thermal cleavage of the NN bond to produce tertiary amines, which are applicable as thermal latent base catalysts for epoxides, epoxide/acid anhydride system, and epoxide/thiol system, and because some of the aminimide derivatives such as benzimides, aminimides possessing PhCON − N + moieties, undergo photolysis to produce tertiary amines, that can be utilized as photobase catalysts for the epoxide/thiol system …”
Section: Introductionmentioning
confidence: 99%